Comparison of nickel and chromium ion release using four different commercially available mouthwashes on orthodontic brackets and wires: An In vitro study - Purva Verma; Ashwin Mathew George (Journal of International Clinical Dental Research Organization, 2022)
Aim: Ions such as nickel and chromium which form the main component of most alloys used in orthodontics are released from orthodontic wires and appliances and can cause allergic reactions and cytotoxicity. The release of ions increases with the intake of fluids. Our study aimed to assess the release of nickel and chromium ions from nickel titanium orthodontic wires following the use of four common mouthwashes. Materials and Methods: The orthodontic appliances were immersed in Amflor Oral Rinse (Fluoridated), Listerine Cool Mint Mouthwash (Alcohol Based), Colgate PlaxMouthwash (nonalcoholic), and Herbal Mouthwash (natural extracts) for 24 h. The samples were collected at four-time intervals and optical emission spectroscopy served to quantify the amount of released ions. Results: The results showed an increase in the release of nickel and chromium ions in all mouthwashes. The release of nickel ions was the highest in Amflor and the lowest in herbal mouthwash. Chromium ion release was highest with Amflor mouthwash. Conclusion: Fluoridated mouth rinses causes increased release of ions while herbal mouthwashes causing least release. Care must be taken while prescribing mouthwashes to sensitized patients.